Computational analysis of spiro-oxindole inhibitors of the MDM2-p53 interaction: insights and selection of novel inhibitors. Issue 2 (1st February 2016) - Huang, Wei; Cai, Lulu; Chen, Can; Xie, Xin; Zhao, Qiong; Zhao, Xing; Zhou, Hong-yun; Han, Bo; Peng, Cheng
Abstract : Since MDM2 is an inhibitor of the p53 tumor suppressor, disrupting the MDM2-p53 interaction is a promising approach for cancer therapy. Here, we used molecular dynamics simulations followed by free energy decomposition analysis to study conformational changes in MDM2 induced by three known spiro-oxindole inhibitors. Analysis of individual energy terms suggests that van der Waals and electrostatic interactions explain much of the binding affinities of these inhibitors. Binding free energies calculated for the three inhibitors using the molecular mechanics-generalized Born surface area model were consistent with experimental data, suggesting the validity of this approach. Based on this structure-function analysis, several novel spiro-oxindole derivatives were selected and evaluated for their ability to block the MDM2-p53 interaction in vitro . These results suggest that combining in silico and experimental techniques can provide insights into the structure-function relationships of MDM2 inhibitors and guide the rational design of anticancer drugs targeting the MDM2-p53 interaction.